Virtual screening assisted identification of a phytocompound as potent inhibitor against Candida lusitaniae; an in-silico study - Rimsha Timotheous; Habiba Naz; Usman Arif; Momna Toqeer Dar; Muhammad Farhan Sarwar; Mudassar Fareed Awan; Sajed Ali; Safia Obaidur Rab (BMC Infectious Diseases)
Abstract Candida lusitaniae is one of the fungal species which causes serious health illnesses including peritonitis, vaginitis and fungemia, among others. Several antifungal drugs have been designed to tackle its infections but their efficacy is still questionable due to their associated side effects. Hence, there is a need to design those drugs which possess comparatively higher degree of therapeutic potential. Phytochemicals were selected in this regard because these compounds which satisfactorily follow this criteria as, their therapeutic index is comparatively larger than the synthetic drugs. Considering this fact, different phyto-compounds were opted in this research work to estimate their therapeutic efficiency against the secreted aspartyl proteinase (SAP) of C. lusitaniae since, it assists this pathogen in developing the infections. Initially, the structure of SAP was modelled for subsequent docking analysis. The results of molecular docking suggested that three compounds, opelconazole, daidzin 4'0-glucuronide and naringin exhibited better docking scores. Afterwards, ADME analysis of all these four compounds was performed to comprehend their drug-likeness attributes. The results of ADME analysis revealed that only the daidzin 4'0-glucuronide followed all the required parameters. Lastly, MD simulations were conducted in which top three compounds in context of docking scores along three approved anti-fungal drugs in complex with SAP were incorporated for the comparative analysis. The overall results of MD simulations suggested that daidzin 4'0-glucuronide exhibited comparatively better results. This outcome indicated that this particular compound not only showed better binding affinity with SAP during docking analysis and fulfilled all of the drug-likeness moieties among other compounds but also, displayed better simulation results, leading to a conclusion that daidzin 4'0-glucuronide could be a potential drug candidate against C. lusitaniae. However, its real-time efficacy could only be validated in clinical settings.